The Role Of The Navy In Algerian-French Relation During The 11th Century (Ah/17thad)Through Correspondence And Treaties –An Archival Analytical Stydy (مجلة الواحات للبحوث والدراسات, 2023)
Abstract: It Is Well Established That The Topic Of Algeria And France  Relations In The Modern Period Is Considered One Of The Most Important Topics That Is Worthy Of Study And Analysis. The Backbone Of These Interactions And Their Manifestations Is Algerian Maritime Activity, Particularly During The Seventeenth Century, Which Was Known To Dominate The Sea. Furthermore, Algeria Is Located On The Routes And Corridors Of The Western Basin Of The Mediterranean, Which Imposed On France The Necessity Of Adapting Peace Treaties To Protect Its Trade And Ships. By Referring To The Entirety Of The Treaties Concluded Between The Two Countries During This Period, We Find That Algeria's Seas And Sailors Were The Reason For Directing These Treaties, Either With Success Or Failure, As Evidenced By Correspondence Between The Two Countries. KEYWORDS: Maritime Activity. Ottoman Era. Seventeenth Century AD. French Algerian  Relations. Correspondance Treaties.